2016
DOI: 10.2352/issn.2470-1173.2016.16.hvei-125
|View full text |Cite
|
Sign up to set email alerts
|

Review on using physiology in quality of experience

Abstract: In the area of Quality of Experience (QoE), one challenge is to design test methodologies in order to evaluate the perceived quality of multimedia content delivered through technical systems. Traditionally, this evaluation is done using subjective opinion tests. However, sometimes it is difficult for observers to communicate the experienced quality through the given scale. Furthermore, those tests do not give insights into how the user is reacting on an internal physiological level. To overcome these issues, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 31 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…There have been numerous attempts to use human physiological measures as indices for presence (e.g., Meehan et al, 2002;Arndt et al, 2016), and several different types of measures have been identified. These physiological indices can be coarsely divided into two families: brain-related and not brain-related.…”
Section: Use Of Physiological Measuresmentioning
confidence: 99%
“…There have been numerous attempts to use human physiological measures as indices for presence (e.g., Meehan et al, 2002;Arndt et al, 2016), and several different types of measures have been identified. These physiological indices can be coarsely divided into two families: brain-related and not brain-related.…”
Section: Use Of Physiological Measuresmentioning
confidence: 99%
“…Although EEG currently appears to be the psychophysiological method that is most widely used in quality assessment, also other measurement methods such as near-infrared spectroscopy are studied and show promising results [24]. For more thorough reviews on this topic we refer the reader to [8,16,22]. In [42] the potential on how to use different assessment methods in the context of immersiveness as a part of QoE are discussed.…”
Section: State-of-the-art Of Physiological Measurements In Quality Asmentioning
confidence: 99%
“…As a potential remedy for these flaws of psychophysical quality assessment and in order to shed light on the cognitive processes underlying quality formations, researchers recently started to study psychophysiological approaches to quality assessment [8,16,22]. These methods aim at bypassing or complementing overt responses of subjects by the measurement of physiological responses that are related to perceived quality.…”
Section: Introductionmentioning
confidence: 99%
“…The implicit methods usually record subject's brain activities or peripheral physiological activities during stimuli representation directly. The electroencephalography (EEG) is a kind of noninvasive technique to record electrical activities of the brain with a high temporal resolution . EEG measurement is even more advisable than subjective measurement, because it records a nonconscious quality evaluation processing in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…The electroencephalography (EEG) is a kind of noninvasive technique to record electrical activities of the brain with a high temporal resolution. 18 EEG measurement is even more advisable than subjective measurement, because it records a nonconscious quality evaluation processing in the brain. The analysis of EEG data contains event-related potentials (ERPs) and frequency band power.…”
Section: Introductionmentioning
confidence: 99%